Hippocrates in context : papers read at the XIth International Hippocrates Colloquium, University of Newcastle upon Tyne, 27-31 August 2002 - Eijk, Ph. J. van der (Studies in Ancient Medicine, 2005)
This collection of papers studies the Hippocratic writings in their relationship to the intellectual, social, cultural and literary context in which they were written. 'Context' includes not only the Greek world, but also the medical thought and practice of other civilisations in the Mediterranean, such as Babylonian and Egyptian medicine. A further point of interest are the relations between the Hippocratic writings and 'non-Hippocratic' medical authors of the fifth and fourth century BCE, such as Diocles of Carystus, Praxagoras of Cos, as well as Plato, Aristotle and Theophrastus. The collection further includes studies of some of the less well-known works in the Hippocratic Corpus, such as Internal Affections , On the Eye , and Prorrheticon . And finally, a number of papers are devoted to the impact and reception of Hippocratic thought in later antiquity and the early modern period.